Lawyers and ethics in legal profession: an overview / Nurul Hidayah Basiran and Zuhainie Zull Kafli - Basiran, Nurul Hidayah; Zull Kafli, Zuhainie (2008)
Legal Profession itself is a vast topic. The preamble to the Bar Council Malaysia's Legal Profession Act 1976, introduces the interpretation of the legal profession with the words, "Advocate and solicitor of the High Court admitted and enrolled under this Act or under any written law prior to the coming into operation of this Act". An Advocate and solicitor are also known as Barrister and solicitor, attorney or lawyer. Lawyers should promote the public interest, serve the cause of justice, be faithful to the client's trust, maintain the authority, be courteous and candid with others and be true to good conscience. Lawyers are more than only a citizen. They are qualified person in the Judicial and Legal service. So, they are obliged to serve justice and fairness in the most ethical ways like what was laid down under several regulations. However, the professionalism of lawyers was seen as a joke by the public recently as there are many issues and conflicts arise about their unethical manner in the legal profession. These are discussed throughout the chapters with references to several regulations that covered the ethics of lawyers in their profession, and also with views from other countries which has similar rules. Some arguments and comments of different people in different areas are also included. This opens up to debates over the effectiveness of the existing laws that safeguarded the lawyer's ethics in the country. In addition to that, recommendations are given to fill in some lacuna that is found in the effectiveness of the rules and other measures, to make sure that the justice and fairness could be served thoroughly by the honest lawyers.